Relating quality changes to storage time for baled alfalfa - W.K. Coblentz; J.O. Fritz; K.K. Bolsen; R.C. Cochran (Kansas Agricultural Experiment Station Research Reports, 1995)
The relationships between storage time and several chemical indices for forage quality were established for alfalfa hay baled at two moisture levels (29.9 and 19.7%) in conventional and laboratory bale s made at 1.0, 1.5, and 2.0 times the density o f parent, conventional bales. Bales were sampled after 0, 4, 11, 22, and 60 days. For the high-moisture bales, most quality indices indicated substantial nutrient loss early in the storage period, particularly between days 4 and 11, with little change after 22 days. A nonlinear mathematical model was constructed to describe how neutral detergent fiber and several other quality indices changed with storage time. Acid detergent fiber was related poorly to storage time. Little change occurred in the low (19.7%) moisture bales.
Keywords: Cattlemen& #x27; s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Alfalfa; Bale density; Hay; Laboratory bales; Storage